A Linear Programming Approach to Aggregate Scheduling - Fuller, Jack (Academy of Management Journal, 1975)
The article discusses the feasibility of using linear programming for production planning by a medium-sized truck body manufacturer. Linear programming was chosen due to the realism of the necessary assumptions. A linear programming model was adapted for scheduling production and work force levels for one particular type of truck body produced by the firm on a production run basis. A Mathematical Programming Systems (MPS) package was used to obtain the solution of this linear programming problem. The output of the program was a schedule of the monthly employment and production rates for a six-month period of time. A new production forecast was prepared at the end of the first month and the program was rerun with updated information to provide a schedule for the following six months.